2014
DOI: 10.1111/cch.12157
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of interventions to improve feeding difficulties in children with autism spectrum disorders: a systematic review and meta‐analysis

Abstract: The reviewed literature consisted primarily of low-level evidence. Favourable intervention outcomes were observed in terms of increasing volume, but not necessarily variety of foods consumed in young children with ASD and feeding difficulties. Further research in the form of prospective randomized trials to further demonstrate experimental effect in this area is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 54 publications
3
40
0
Order By: Relevance
“…A large proportion of studies relied on extinction‐based procedures to decrease IMB (i.e., greater than 80% of treatments based on the results of a functional analysis, and greater than 90% not based on a functional analysis, arranged escape extinction procedurally). This result, combined with other findings (e.g., Marshall et al, ; Saini et al, in press; Sharp et al, ; Silbaugh et al, ), emphasizes the role of escape as a reinforcer for IMB and the efficacy of escape extinction as a treatment component. Studies that have evaluated the efficacy of escape extinction relative to other treatment components have repeatedly shown that increased acceptance and a concomitant reduction in IMB is often due to the escape extinction component (LaRue et al, ; Piazza, Patel, Gulotta, Sevin, & Layer, ; Reed et al, ).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…A large proportion of studies relied on extinction‐based procedures to decrease IMB (i.e., greater than 80% of treatments based on the results of a functional analysis, and greater than 90% not based on a functional analysis, arranged escape extinction procedurally). This result, combined with other findings (e.g., Marshall et al, ; Saini et al, in press; Sharp et al, ; Silbaugh et al, ), emphasizes the role of escape as a reinforcer for IMB and the efficacy of escape extinction as a treatment component. Studies that have evaluated the efficacy of escape extinction relative to other treatment components have repeatedly shown that increased acceptance and a concomitant reduction in IMB is often due to the escape extinction component (LaRue et al, ; Piazza, Patel, Gulotta, Sevin, & Layer, ; Reed et al, ).…”
Section: Discussionsupporting
confidence: 67%
“…Several reviews and meta‐analyses have demonstrated the robust effects of behavioral treatments for feeding problems, including increasing oral intake (i.e., calories consumed), increasing diet variety, and decreasing inappropriate mealtime behavior (IMB; Marshall, Ware, Ziviani, Hill, & Dodrill, ; Seubert, Fryling, Wallace, Jiminez, & Meier, ; Sharp, Jaquess, Morton, & Herzinger, ; Sharp et al, ; Silbaugh et al, ). In fact, treatments based on applied behavior analysis are the only ones with strong empirical support for addressing mealtime difficulties (Kerwin, ; Volkert & Piazza, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study we used a quantitative measure of food selectivity to assess the number of different foods a child refuses, not the volume of food a child would accept. In a recent systematic review and meta-analysis of interventions for children up to 6 years of age, Marshall et al concluded that while there is evidence for interventions that increase the amount of food eaten, less evidence exists for interventions that increase food variety (Marshall, Ware, Ziviani, Hill, & Dodrill, 2014). In a large study of children aged 3–12 years, Laud et al (2009) demonstrated the efficacy of an intensive interdisciplinary behavioral program to decrease food refusal and increase variety in 46 children with severe feeding problems, several of whom had medical comorbidities, and were hospitalized on an inpatient facility or enrolled in an intensive day treatment program (Laud, Girolami, Boscoe, & Gulotta, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, research is also needed to ascertain whether minimizing noxious environmental sensory stimuli or using sensory integration interventions or strategies to decrease sensory sensitivities results in fewer mealtime problem behaviors. Use of sensory strategies to enhance food acceptance and reduce undesirable mealtime behaviors is an alternative or complementary approach to the most commonly used behavioral interventions (Marshall, Ware, Ziviani, Hill, & Dodrill, 2015). Stein et al (2012) explored the effect of sensory sensitivities on the dental experience of children with ASD.…”
Section: Discussionmentioning
confidence: 99%